2022
DOI: 10.1093/mnras/stac2935
|View full text |Cite
|
Sign up to set email alerts
|

Mean opacities of a strongly magnetized high-temperature plasma

Abstract: Geometry and dynamical structure of emission regions in accreting pulsars are shaped by the interplay between gravity, radiation, and strong magnetic field, which significantly affects the opacities of a plasma and radiative pressure under such extreme conditions. Quantitative consideration of magnetic plasma opacities is, therefore, an essential ingredient of any self-consistent modeling of emission region structure of X-ray pulsars. We present results of computations of the Rosseland and Planck mean opacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In these cases, the surface magnetic fields determined from the AC emission properties (e.g., critical luminosity, CRSF, and maximum luminosity) are very different from (and most likely much stronger than) the dipole fields determined from torque models. However, recent studies (Suleimanov et al 2022) show that the high magnetic field increases the electron-positron pairs, which compensate the opacity reduction due to the high magnetic field, such that…”
Section: Multipole and Dipole Magnetic Fields Of Pulxsmentioning
confidence: 99%
“…In these cases, the surface magnetic fields determined from the AC emission properties (e.g., critical luminosity, CRSF, and maximum luminosity) are very different from (and most likely much stronger than) the dipole fields determined from torque models. However, recent studies (Suleimanov et al 2022) show that the high magnetic field increases the electron-positron pairs, which compensate the opacity reduction due to the high magnetic field, such that…”
Section: Multipole and Dipole Magnetic Fields Of Pulxsmentioning
confidence: 99%
“…When the luminosity exceeds the critical value of ∼10 37 erg s −1 (Mushtukov et al 2015), the radiation-dominated shock inside the column decelerates the accretion flow, and the kinetic energy is converted to X-rays via the Comptonization of the seed photons emitted from the surface of the neutron star (Becker & Wolff 2005Odaka et al 2014). The power-law-like spectrum, accompanied by a cutoff feature, which is typical of X-ray pulsars, has been interpreted as a consequence of bulk and thermal Comptonization in the accretion column, with the substantial modification of scattering cross sections due to the presence of the magnetic field (Daugherty & Harding 1986;Mushtukov et al 2016;Schwarm et al 2017;Suleimanov et al 2022). Some previous studies have revealed that the model satisfactorily explains the X-ray spectra of X-ray pulsars (e.g., Wolff et al 2016;West et al 2017), based on the 1D radiative transfer equation.…”
Section: Introductionmentioning
confidence: 99%
“…The theory of neutrino emission from bright XRPs requires the development of an accurate model of accretion column, which accounts for mechanisms of magnetic opacity (Suleimanov et al 2022(Suleimanov et al , 2023 L X L ν Luminosity, erg s -1 mass accretion rate, g s -1…”
Section: Introductionmentioning
confidence: 99%